2019
DOI: 10.1111/jmwh.12957
|View full text |Cite
|
Sign up to set email alerts
|

Midwifery Care for Transfeminine Individuals

Abstract: This article focuses on the provision of gender-affirming care and preventive care for transfeminine individuals-those assigned male at birth who identify as female or on the feminine spectrum. To meet the learning needs of health care providers less familiar with gender-affirming care, this article begins with an overview of gender identity concepts. Initiation and management of feminizing gender-affirming hormone therapy is then covered in detail, including common gender-affirming medications and their adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…In bedside nursing, primary nursing teams are established and nurses are assigned with different tasks according to their working ability and patients' needs so that each patient is nursed by a primary nurse. In addition, the implementation of three-level quality control and supervision system can effectively improve the working ability of the nursing staff, and reduce or avoid the occurrence of clinical adverse events, thereby improving the nursing quality and ensuring the clinical treatment effect [ 18 , 19 ]. In this study, after the implementation of combined nursing intervention for patients with gastrointestinal diseases, the VAS scores in the research group were significantly lower than those in the reference group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In bedside nursing, primary nursing teams are established and nurses are assigned with different tasks according to their working ability and patients' needs so that each patient is nursed by a primary nurse. In addition, the implementation of three-level quality control and supervision system can effectively improve the working ability of the nursing staff, and reduce or avoid the occurrence of clinical adverse events, thereby improving the nursing quality and ensuring the clinical treatment effect [ 18 , 19 ]. In this study, after the implementation of combined nursing intervention for patients with gastrointestinal diseases, the VAS scores in the research group were significantly lower than those in the reference group.…”
Section: Discussionmentioning
confidence: 99%
“…The team leaders need to supervise the work of primary nurses to correct deficiencies. For the department leaders, they should supervise the daily work of primary nursing, conduct a check-up system to comprehensively grasp the causes of clinical adverse events, analyze the risk factors affecting the quality of care, and fundamentally ensure the smooth development of nursing services [ 18 , 20 , 21 ]. This study showed that the incidence of clinical adverse events in the research group was significantly lower than that in the reference group, suggesting that the combined nursing intervention can effectively improve the responsibility consciousness of nursing staff and reduce the incidence of clinical adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Nurse‐midwives may be caring for transgender people in their practices, and with the appropriate education, the American College of Nurse‐Midwives endorses transgender people's care and hormone treatment as part of the midwifery scope of practice . The Journal of Midwifery and Women's Health has had several excellent recent review articles on the care of transgender persons with education and practice guideline resources clearly identified . Many transgender individuals may be seeking hormone treatment, and the midwifery model of care of respectful practice and shared decision making makes midwives poised to be important health care providers to this population.…”
Section: Featured Reviewmentioning
confidence: 99%
“…The inclusion of care for transgender and non‐binary people in midwifery and women's health care is affirming to communities that have long been cast as outsiders. The recent discussions in this journal of care for trans feminine 1 and trans masculine 2 individuals, the 2018 editorial on “gender‐neutral” language, 3 and the updated American College of Nurse‐Midwives Core Competencies for Basic Midwifery Practice 4 are heartening, although the latter falls behind in naming and describing both gender care and its competencies. As this journal's editors mention, language is important and evolves; the same goes for ethical discussions of all care, but in particular for those communities that experience multiple social and political marginalizations.…”
mentioning
confidence: 99%